DSP - Z-Transform Introduction and Properties

Discrete Time Fourier Transform(DTFT) exists for energy and power signals. Z-transform also exists for neither energy nor Power (NENP) type signal, up to a certain extent only. The replacement \(z=e^{jw}\) is used for Z-transform to DTFT conversion only for absolutely summable signal.

So, the Z-transform of the discrete time signal x(n) in a power series can be written as −

$$X(z) = \sum_{n-\infty}^\infty x(n)Z^{-n}$$

The above equation represents a two-sided Z-transform equation.

Generally, when a signal is Z-transformed, it can be represented as −

$$X(Z) = Z[x(n)]$$

Or $$x(n) \longleftrightarrow X(Z)$$

If it is a continuous time signal, then Z-transforms are not needed because Laplace transformations are used. However, Discrete time signals can be analyzed through Z-transforms only.

Mapping of S Plane onto Z Plane - Video tutorial

Region of Convergence

Region of Convergence is the range of complex variable Z in the Z-plane. The Z- transformation of the signal is finite or convergent. So, ROC represents those set of values of Z, for which X(Z) has a finite value.

Properties of ROC

  • ROC does not include any pole.
  • For right-sided signal, ROC will be outside the circle in Z-plane.
  • For left sided signal, ROC will be inside the circle in Z-plane.
  • For stability, ROC includes unit circle in Z-plane.
  • For Both sided signal, ROC is a ring in Z-plane.
  • For finite-duration signal, ROC is entire Z-plane.

The Z-transform is uniquely characterized by −

  • Expression of X(Z)
  • ROC of X(Z)

Signals and their ROC

x(n) X(Z) ROC
$$\delta(n)$$ $$1$$ Entire Z plane
$$U(n)$$ $$1/(1-Z^{-1})$$ Mod(Z)>1
$$a^nu(n)$$ $$1/(1-aZ^{-1})$$ Mod(Z)>Mod(a)
$$-a^nu(-n-1)$$ $$1/(1-aZ^{-1})$$ Mod(Z)<Mod(a)
$$na^nu(n)$$ $$aZ^{-1}/(1-aZ^{-1})^2$$ Mod(Z)>Mod(a)
$$-a^nu(-n-1)$$ $$aZ^{-1}/(1-aZ^{-1})^2$$ Mod(Z)<Mod(a)
$$U(n)\cos \omega n$$ $$(Z^2-Z\cos \omega)/(Z^2-2Z \cos \omega +1)$$ Mod(Z)>1
$$U(n)\sin \omega n$$ $$(Z\sin \omega)/(Z^2-2Z \cos \omega +1)$$ Mod(Z)>1

Example

Let us find the Z-transform and the ROC of a signal given as \(x(n) = \lbrace 7,3,4,9,5\rbrace\), where origin of the series is at 3.

Solution − Applying the formula we have −

\(X(z) = \sum_{n=-\infty}^\infty x(n)Z^{-n}\)

\(= \sum_{n=-1}^3 x(n)Z^{-n}\)

\(= x(-1)Z+x(0)+x(1)Z^{-1}+x(2)Z^{-2}+x(3)Z^{-3}\)

\(= 7Z+3+4Z^{-1}+9Z^{-2}+5Z^{-3}\)

ROC is the entire Z-plane excluding Z = 0, ∞, -∞

DSP - Z-Transform Properties

In this chapter, we will understand the basic properties of Z-transforms.

Linearity

It states that when two or more individual discrete signals are multiplied by constants, their respective Z-transforms will also be multiplied by the same constants.

Mathematically,

$$a_1x_1(n)+a_2x_2(n) = a_1X_1(z)+a_2X_2(z)$$

Proof − We know that,

\(X(Z) = \sum_{n=-\infty}^\infty x(n)Z^{-n}\)

\(= \sum_{n=-\infty}^\infty (a_1x_1(n)+a_2x_2(n))Z^{-n}\)

\(= a_1\sum_{n = -\infty}^\infty x_1(n)Z^{-n}+a_2\sum_{n = -\infty}^\infty x_2(n)Z^{-n}\)

\(= a_1X_1(z)+a_2X_2(z)\) (Hence Proved)

Here, the ROC is \(ROC_1\bigcap ROC_2\).

Time Shifting

Time shifting property depicts how the change in the time domain in the discrete signal will affect the Z-domain, which can be written as;

$$x(n-n_0)\longleftrightarrow X(Z)Z^{-n}$$

Or $$x(n-1)\longleftrightarrow Z^{-1}X(Z)$$

Proof

Let \(y(P) = X(P-K)\)

\(Y(z) = \sum_{p = -\infty}^\infty y(p)Z^{-p}\)

\(= \sum_{p = -\infty}^\infty (x(p-k))Z^{-p}\)

Let s = p-k

\(= \sum_{s = -\infty}^\infty x(s)Z^{-(s+k)}\)

\(= \sum_{s = -\infty}^\infty x(s)Z^{-s}Z^{-k}\)

\(= Z^{-k}[\sum_{s=-\infty}^\infty x(m)Z^{-s}]\)

\(= Z^{-k}X(Z)\) (Hence Proved)

Here, ROC can be written as Z = 0 (p>0) or Z = ∞(p<0)

Example

U(n) and U(n-1) can be plotted as follows

Time Shifting Example
Time Shifting Example.

Z-transformation of U(n) cab be written as;

$$\sum_{n = -\infty}^\infty [U(n)]Z^{-n} = 1$$

Z-transformation of U(n-1) can be written as;

$$\sum_{n = -\infty}^\infty [U(n-1)]Z^{-n} = Z^{-1}$$

So here \(x(n-n_0) = Z^{-n_0}X(Z)\) (Hence Proved)

Time Scaling

Time Scaling property tells us, what will be the Z-domain of the signal when the time is scaled in its discrete form, which can be written as;

$$a^nx(n) \longleftrightarrow X(a^{-1}Z)$$

Proof

Let \(y(p) = a^{p}x(p)\)

\(Y(P) = \sum_{p=-\infty}^\infty y(p)Z^{-p}\)

\(= \sum_{p=-\infty}^\infty a^px(p)Z^{-p}\)

\(= \sum_{p=-\infty}^\infty x(p)[a^{-1}Z]^{-p}\)

\(= X(a^{-1}Z)\)(Hence proved)

ROC: = Mod(ar1) < Mod(Z) < Mod(ar2) where Mod = Modulus

Example

Let us determine the Z-transformation of \(x(n) = a^n \cos \omega n\) using Time scaling property.

Solution

We already know that the Z-transformation of the signal \(\cos (\omega n)\) is given by −

$$\sum_{n=-\infty}^\infty(\cos \omega n)Z^{-n} = (Z^2-Z \cos \omega)/(Z^2-2Z\cos \omega +1)$$

Now, applying Time scaling property, the Z-transformation of \(a^n \cos \omega n\) can be written as;

\(\sum_{n=-\infty}^\infty(a^n\cos \omega n)Z^{-n} = X(a^{-1}Z)\)

\(= [(a^{-1}Z)^2-(a^{-1}Z \cos \omega n)]/((a^{-1}Z)^2-2(a^{-1}Z \cos \omega n)+1)\)

\(= Z(Z-a \cos \omega)/(Z^2-2az \cos \omega+a^2)\)

Successive Differentiation

Successive Differentiation property shows that Z-transform will take place when we differentiate the discrete signal in time domain, with respect to time. This is shown as below.

$$\frac{dx(n)}{dn} = (1-Z^{-1})X(Z)$$

Proof

Consider the LHS of the equation − \(\frac{dx(n)}{dn}\)

\(= \frac{[x(n)-x(n-1)]}{[n-(n-1)]}\)

\(= x(n)-X(n-1)\)

\(= x(Z)-Z^{-1}x(Z)\)

\(= (1-Z^{-1})x(Z)\) (Hence Proved)

ROC: R1< Mod (Z) <R2

Example

Let us find the Z-transform of a signal given by \(x(n) = n^2u(n)\)

By property we can write

\(Zz[nU(n)] = -Z\frac{dZ[U(n)]}{dz}\)

\(= -Z\frac{d[\frac{Z}{Z-1}]}{dZ}\)

\(= Z/((Z-1)^2\)

\(= y(let)\)

Now, Z[n.y] can be found out by again applying the property,

\(Z(n,y) = -Z\frac{dy}{dz}\)

\(= -Z\frac{d[Z/(Z-1)^3]}{dz}\)

\(= Z(Z+1)/(Z-1)^2\)

Convolution

This depicts the change in Z-domain of the system when a convolution takes place in the discrete signal form, which can be written as −

$$x_1(n)*x_2(n) \longleftrightarrow X_1(Z).X_2(Z)$$

Proof

\(X(Z) = \sum_{n = -\infty}^\infty x(n)Z^{-n}\)

\(= \sum_{n=-\infty}^\infty[\sum_{k = -\infty}^\infty x_1(k)x_2(n-k)]Z^{-n}\)

\(= \sum_{k = -\infty}^\infty x_1(k)[\sum_n^\infty x_2(n-k)Z^{-n}]\)

\(= \sum_{k = -\infty}^\infty x_1(k)[\sum_{n = -\infty}^\infty x_2(n-k)Z^{-(n-k)}Z^{-k}]\)

Let n-k = l, then the above equation cab be written as −

\(X(Z) = \sum_{k = -\infty}^\infty x_1(k)[Z^{-k}\sum_{l=-\infty}^\infty x_2(l)Z^{-l}]\)

\(= \sum_{k = -\infty}^\infty x_1(k)X_2(Z)Z^{-k}\)

\(= X_2(Z)\sum_{k = -\infty}^\infty x_1(Z)Z^{-k}\)

\(= X_1(Z).X_2(Z)\) (Hence Proved)

ROC:\(ROC\bigcap ROC2\)

Example

Let us find the convolution given by two signals

\(x_1(n) = \lbrace 3,-2,2\rbrace\) ...(eq. 1)

\(x_2(n) = \lbrace 2,0\leq 4\quad and\quad 0\quad elsewhere\rbrace\) ...(eq. 2)

Z-transformation of the first equation can be written as;

\(\sum_{n = -\infty}^\infty x_1(n)Z^{-n}\)

\(= 3-2Z^{-1}+2Z^{-2}\)

Z-transformation of the second signal can be written as;

\(\sum_{n = -\infty}^\infty x_2(n)Z^{-n}\)

\(= 2+2Z^{-1}+2Z^{-2}+2Z^{-3}+2Z^{-4}\)

So, the convolution of the above two signals is given by −

\(X(Z) = [x_1(Z)^*x_2(Z)]\)

\(= [3-2Z^{-1}+2Z^{-2}]\times [2+2Z^{-1}+2Z^{-2}+2Z^{-3}+2Z^{-4}]\)

\(= 6+2Z^{-1}+6Z^{-2}+6Z^{-3}+...\quad...\quad...\)

Taking the inverse Z-transformation we get,

\(x(n) = \lbrace 6,2,6,6,6,0,4\rbrace\)

Initial Value Theorem

If x(n) is a causal sequence, which has its Z-transformation as X(z), then the initial value theorem can be written as;

$$X(n)(at\quad n = 0) = \lim_{z \to \infty} X(z)$$

Proof − We know that,

$$X(Z) = \sum_{n = 0} ^\infty x(n)Z^{-n}$$

Expanding the above series, we get;

\(= X(0)Z^0+X(1)Z^{-1}+X(2)Z^{-2}+...\quad...\)

\(= X(0)\times 1+X(1)Z^{-1}+X(2)Z^{-2}+...\quad...\)

In the above case if Z → ∞ then \(Z^{-n}\rightarrow 0\) (Because n>0)

Therefore, we can say;

\(\lim_{z \to \infty}X(z) = X(0)\) (Hence Proved)

Final Value Theorem

Final Value Theorem states that if the Z-transform of a signal is represented as X(Z) and the poles are all inside the circle, then its final value is denoted as x(n) or X(∞) and can be written as −

$$X(\infty) = \lim_{n \to \infty}X(n) = \lim_{z \to 1}[X(Z)(1-Z^{-1})]$$

Conditions

  • It is applicable only for causal systems.
  • \(X(Z)(1-Z^{-1})\) should have poles inside the unit circle in Z-plane.

Proof − We know that

\(Z^+[x(n+1)-x(n)] = \lim_{k \to \infty}\sum_{n=0}^kZ^{-n}[x(n+1)-x(n)]\)

\(\Rightarrow Z^+[x(n+1)]-Z^+[x(n)] = \lim_{k \to \infty}\sum_{n=0}^kZ^{-n}[x(n+1)-x(n)]\)

\(\Rightarrow Z[X(Z)^+-x(0)]-X(Z)^+ = \lim_{k \to \infty}\sum_{n = 0}^kZ^{-n}[x(n+1)-x(n)]\)

Here, we can apply advanced property of one-sided Z-Transformation. So, the above equation can be re-written as;

$$Z^+[x(n+1)] = Z[X(2)^+-x(0)Z^0] = Z[X(Z)^+-x(0)]$$

Now putting z = 1 in the above equation, we can expand the above equation −

$$\lim_{k \to \infty}{[x(1)-x(0)+x(6)-x(1)+x(3)-x(2)+...\quad...\quad...+x(x+1)-x(k)]}$$

This can be formulated as;

\(X(\infty) = \lim_{n \to \infty}X(n) = \lim_{z \to 1}[X(Z)(1-Z^{-1})]\)(Hence Proved)

Example

Let us find the Initial and Final value of x(n) whose signal is given by

$$X(Z) = 2+3Z^{-1}+4Z^{-2}$$

Solution − Let us first, find the initial value of the signal by applying the theorem

\(x(0) = \lim_{z \to \infty}X(Z)\)

\(= \lim_{z \to \infty}[2+3Z^{-1}+4Z^{-2}]\)

\(= 2+(\frac{3}{\infty})+(\frac{4}{\infty}) = 2\)

Now let us find the Final value of signal applying the theorem

\(x(\infty) = \lim_{z \to \infty}[(1-Z^{-1})X(Z)]\)

\(= \lim_{z \to \infty}[(1-Z^{-1})(2+3Z^{-1}+4Z^{-2})]\)

\(= \lim_{z \to \infty}[2+Z^{-1}+Z^{-2}-4Z^{-3}]\)

\(= 2+1+1-4 = 0\)

Some other properties of Z-transform are listed below

Differentiation in Frequency

It gives the change in Z-domain of the signal, when its discrete signal is differentiated with respect to time.

$$nx(n)\longleftrightarrow -Z\frac{dX(z)}{dz}$$

Its ROC can be written as;

$$r_2< Mod(Z)< r_1$$

Example

Let us find the value of x(n) through Differentiation in frequency, whose discrete signal in Z-domain is given by $$x(n)\longleftrightarrow X(Z) = log(1+aZ^{-1})$$

By property, we can write that

\(nx(n)\longleftrightarrow -Z\frac{dx(Z)}{dz}\)

\(= -Z[\frac{-aZ^{-2}}{1+aZ^{-1}}]\)

\(= (aZ^{-1})/(1+aZ^{-1})\)

\(= 1-1/(1+aZ^{-1})\)

\(nx(n) = \delta(n)-(-a)^nu(n)\)

\(\Rightarrow x(n) = 1/n[\delta(n)-(-a)^nu(n)]\)

Multiplication in Time

It gives the change in Z-domain of the signal when multiplication takes place at discrete signal level.

$$x_1(n).x_2(n)\longleftrightarrow(\frac{1}{2\Pi j})[X_1(Z)*X_2(Z)]$$


Home work

  1. Determine the Z-transform of the following sequences and find ROC
    i. \(x(n) = (n + 2) (1/2)^n u(n)\)
    ii. \(x(n) = (2/3)^n u(n) + (3/4) u(n - 1)\)
  2. The z-transform of a signal is given by \(X(z) = \frac{1z^{-1} (1 - z^{-4})}{4(1 - z^{-1})^2}\) . Find the final value.